Copper(II) Complexes of Organophoshonic Acids-A Comparative Study - B. Venkateswara Rao; D. M. Puri (E-Journal of Chemistry)
Polynuclear copper(II) derivatives of 1-hydroxyethylidenediphosphonic acid (HEDP), 1-aminoethylidenediphosphonic acid (AEDP, H4L), α-aminobenzylidene diphosphonic acid (ABDP, H4L), 1-amino-2-carboxyethane- 1,1-diphosphonic acid (ACEDP, H5L), 1,3 diaminopropane-1,1,3,3-tetra-phosphonic acid (DAPTP, H8L), Ethylenediamine-N,N'-bis (dimethyl-methylenephosphonic) acid (EDBDMPO, H4L), o-phenylene-diamine-N,N'-bis (dimethylmethylenephosphonic) acid (PDBDMPO, H4L), diethylene triamine –N,N,N',N',N"N-penta (methylene phosphonic) acid (DETAPMPO, H10L) and diethylene triamine –N,N"-bis (dimethyl methylene phosphonic) acid (DETBDMPO, H4L) have been prepared in aqueous medium. The general formula of derivatives from elemental analysis was found to be Cu2L.XH2O (in case of AEDP, ABDP, EDBDMPO, PDBDMPO, DETBDMPO), Cu5L2.XH2O (in case of ACEDP) Cu4L.XH2O, Cu2 H4L. XH2O (in case of DAPTP) and Cu5L.XH2O (in case of DETAPMPO). The electronic spectra have shown them to be six coordinated with slight distortion from octahedral geometry. Antiferromagnetism was inferred from magnetic moment data. Infrared spectral studies were carried out to determine coordination sites. EPR (Electron Paramagnetic Resonance) spectra that supports the presence of tetragonal distortion and antiferromagnetic behaviour, have also been studied.